Analisis Purwarupa Sistem Otomatisasi Penerang Jalan Untuk Menghemat Daya Listrik - Eridani, Dania; Asyauqqi, M. Azka; Prasetijo, Agung Budi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Public street lighting automation is one part of an area or a city development design. The design of public street lightning need to pay attention to several aspects, where one of them is how the public street lighting design is able to save electricity consumption. This research contain several combination of public street light-ing automation designs. It use Arduino Mega 2560 board as the main control board, KY-018 sensor as the sen-sor to detect the environment light intensity, HC-SR501 sensor as the sensor to detect object movement, AC light dimmer as the regulator of the lamp, AC power meter as a measuring device to measure the power con-sumption of the lamp used. The testing mechanism are consist of testing the input and output components in the system and testing the electricity consumption in the circuit design. The results of the research carried out, showed a comparison of the level of electricity consumption from each series of combinations that can be used as a reference for road lighting development planning.